Proton Sponge Analogue of the Tröger's Base: A Compound with Remarkable Enantiomeric Stability. Issue 30 (25th October 2017) - Ozeryanskii, Valery A.; Vlasenko, Marina P.; Pozharskii, Alexander F.; Sergeyev, Sergey; Maes, Bert U. W.; Franck, Philippe; Herrebout, Wouter A.
Abstract: Proton sponge analogue of the Tröger's base (4 ) has been obtained upon treatment of 1‐amino‐4, 5‐bis(dimethylamino)naphthalene with paraformaldehyde. It was found that in contrast to classical Tröger's base1, protonation of4 occurs, at least thermodynamically, exclusively on peri ‐NMe2 groups producing a dication with two chelated [NHN] + hydrogen bonds. This prevents the protonation of the bridge nitrogen atoms, which is responsible for rather easy racemization of1 . Indeed, two enantiomers of4 were resolved by chiral chromatography and their much higher stability in acidic media as compared to1 has been confirmed. Some other properties of base4 including structure, basicity, dynamic NMR behavior, host‐guest interactions and reactions with electrophiles are also discussed. Abstract : Proton sponge residues account for unusual chemistry and both for sterical and chemical inhibition to racemization of new chiral basePSTB (proton sponge Tröger's base). Both neutral as well as doubly‐protonated forms ofPSTB are prone to form host‐guest compounds.